Analysis of peptides and small proteins in preparations of horse milk exosomes, purified on anti-CD81-Sepharose. (June 2021) - Sedykh, Sergey E.; Purvinish, Lada V.; Burkova, Evgeniya E.; Dmitrenok, Pavel S.; Vlassov, Valentin V.; Ryabchikova, Elena I.; Nevinsky, Georgy A.
Abstract: Exosomes are nanovesicles (40–100 nm) involved in intracellular communication. Milk is a unique source of exosomes. In our previous papers, our group was the first to describe horse milk exosomes. Here we show how crude vesicle preparations were obtained from 18 horse milk samples by standard centrifugation, ultracentrifugation, and gel-filtration methods. Transmission electron microscopy and flow cytometry confirmed that exosomes contain tetraspanins on their surface. Affinity chromatography of vesicle preparations on anti-CD81-Sepharose produced extra-purified exosomes with more than 20 peptides and small proteins of 0.8–10 kDa as detected by MALDI-TOF mass spectrometry. The peptides are natural intrinsic components of horse milk exosomes and are not formed either as a result of or during sample preparation. We assume some of the hundreds and thousands of exosome proteins previously described by other authors in milk exosomes by highly sensitive liquid chromatography-mass spectrometry to have been misidentified as full-length proteins.